The intellectual Umbrella for the strategic scenario in business organizations - The Opinions and the Spotlights - العبادي, هاشم فوزي (Journal of Economics and Administrative Sciences, 2012)
Today, more than ever before, the business organizations’ initiatives should seek to design themselves and delivery them to the environment because of its change, and the increasing of uncertainties and the growing opportunities. What is required by the business organizations is that to adopt good approaches to stimulate the modern thinking and non traditional thinking and exploit the valued concepts and overcome the old thinking. Substantially, the scenario planning is the art of thinking about what is unexpected.        Therefore the research’s problem is reflected to answer the following questions:• What is the methodology to build a strategic scenario?• What are the entries of the strategic scenario planning that could be used by the Entrepreneurships?    According to the latest survey conducted by McKenzie company (2009), the scenario planning has been nominated by the executives to be the most important valued tool that helps them to cope with the changing environment. Therefore the importance of this research reflected as follows: • Review of research methodology, including a very contemporary theme (the strategic scenario) to achieve an understanding of conscious and aware of its concepts, objectives and assumptions.• Demonstrate the use of scenario analysis to develop the crisis management and to stimulate the strategic thinking across range of practices, techniques and clear steps and motivating for business organizations to adopt them in shaping their future characteristics and identify the ways to meet their challenges.        The study has reached a set of Summary, the scenario planning provides an ideal interface for the creativity and to examine the business environment, because the process of scenario planning is allowing by its nature to assist the management to create the drives of the business environment and to diagnose the problems that arise due to the tendencies (trends) and the possible changes in this context.